Case report: Reversible brain atrophy with low titer anti-amphiphysin antibodies related to gastric adenocarcinoma - Amano, Ryota; Kim, Yeon-Jeong; Yoshida, Toshikazu; Hara, Makoto; Nakajima, Hideto; Ohtsuka, Toshihisa; Yazawa, Masanobu (Frontiers in Neurology, 2023)
Amphiphysin (AMPH) autoimmunity is associated with a variety of neurological complications, including encephalitis, peripheral neuropathy, myelopathy, and cerebellar syndrome. Its diagnosis is based on clinical neurological deficits and the presence of serum anti-AMPH antibodies. Active immunotherapy, such as intravenous immunoglobulins, steroids, and other immunosuppressive therapies, has been reported to be effective in most patients. However, the extent of recovery varies depending on the case. Herein, we report the case of a 75-year-old woman with semi-rapidly progressive systemic tremors, visual hallucinations, and irritability. Upon hospitalization, she developed a mild fever and cognitive impairment. Brain magnetic resonance imaging (MRI) showed semi-rapidly progressive diffuse cerebral atrophy (DCA) over 3 months, while no clear abnormal intensities were observed. The nerve conduction study revealed sensory and motor neuropathy in the limbs. The fixed tissue-based assay (TBA) failed to detect antineuronal antibodies; however, based on commercial immunoblots, the presence of anti-AMPH antibodies was suspected. Therefore, serum immunoprecipitation was performed, which confirmed the presence of anti-AMPH antibodies. The patient also had gastric adenocarcinoma. High-dose methylprednisolone, and intravenous immunoglobulin were administered and tumor resection was performed, resulting in resolution of the cognitive impairment and improvement in the DCA on the post-treatment MRI. After immunotherapy and tumor resection, the patient's serum was analyzed using immunoprecipitation, which showed a decrease in the level of anti-AMPH antibodies. This case is noteworthy because the DCA showed improvement after immunotherapy and tumor resection. Additionally, this case demonstrates that negative TBA with positive commercial immunoblots do not necessarily indicate false positive results.